2012
DOI: 10.3109/03008207.2012.690793
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of the Healing Tendon: A Comparison of the Effects of Intrasound Therapy and Therapeutic Pulsed Ultrasound

Abstract: Intrasound therapy has a better morphological effect on the healing tendon than LIPUS and may be an option to consider in the treatment of acute tendon injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…17 In this study, though treatment with IST was given twice weekly, there was an appreciable improvement in the primary and secondary outcome measures. A study by Aiyegbusi et al 16 suggested that twice daily treatment was more effective in augmenting healing than once daily treatment. Further studies are needed to determine if a once daily or twice daily treatment with IST would have an even better effect on the clinical and functional outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 In this study, though treatment with IST was given twice weekly, there was an appreciable improvement in the primary and secondary outcome measures. A study by Aiyegbusi et al 16 suggested that twice daily treatment was more effective in augmenting healing than once daily treatment. Further studies are needed to determine if a once daily or twice daily treatment with IST would have an even better effect on the clinical and functional outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The intrasound massager was plugged in, set at the most comfortable intensity for the subject 16 and moved over the affected part of the knee joint in circular motion for 10 minutes with KY-Jelly as a coupling medium. The subjects reported a fine feeling of micromassage and vibrations during the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies on tendon repair using ultrasound follow the recommendation of 1-2 minutes per transducer treated 6,33,34 . The rationale for this treatment is based on previous studies using the same application time or following the recommendations of Oakley 31 and Hoogland…”
Section: Introductionmentioning
confidence: 99%